Governance for Sustainable Water Supply, Sanitation and Hygiene Services in Rural Nepal - Khatri, Bishnu Bahadur; Bhandari, Madan Bahadur (Journal of Development and Administrative Studies, 2019)
Governance for sustainable water supply, sanitation, and hygiene (WASH) services in rural Nepal is a major challenge that requires continuous efforts to improve coordination, delivery of quality interventions, and community participation. Issues related to governance in the water, sanitation, and hygiene (WASH) sectors are globally significant, with the consideration of the functionality of WASH services in rural Nepal. This article explores the relationship between distinct cases and the underlying causes of governance issues in Nepal's WASH sector, emphasizing the need for more effective delivery and response mechanisms. Additionally, this article analyses existing issues related to inclusive governance and the role of community people to ensure inclusive and appropriate WASH governance. The governance framework is shaped by historical practices, existing policies, and socio-cultural values within society. The article also provides a perspective on historical and socio-cultural transformations, policy analysis, and shared learning based on published articles on WASH, governance, sustainability, and development theories. Furthermore, it addresses issues of inclusive participation, decision-making, and financial transparency as integral components of good governance, which play a significant role in ensuring the sustainability of WASH services in communities. In conclusion, this paper asserts that the functionality of WASH services often fails due to inadequate governance, whereas governance is directed by the history of the places and applied development theories and approaches up to the timeframe.